Transformational Leadership and Innovative Work Behavior: The Mediating Role of Work-Family Enrichment - Artiawati; Krismasita Surya Putri; Teresa Regina Tamin (Humanitas: Indonesian Psychological Journal, 2026)
While transformational leadership (TL) is widely recognized as a key driver of innovative work behavior (IWB), empirical evidence on the mediating role of work–family enrichment (WFE) remains inconsistent, particularly in the Indonesian FMCG industry. This study addresses this gap by examining whether WFE mediates the relationship between TL and IWB. A quantitative approach with accidental sampling was employed, involving 101 married employees of X Company and its subsidiaries. TL, IWB, and WFE were measured using the Global Transformational Leadership Scale (Carless et al., 2000), the Innovative Work Behavior Scale (Janssen, 2000), and the Work-Family Enrichment Scale (Carlson et al., 2006). Data were analyzed using path analysis with mediation testing. The results indicate that TL significantly predicts WFE (B = .45; p < .001). However, WFE does not mediate the relationship between TL and IWB (B = .03; p = .471). TL maintains a significant direct effect on IWB (B = .21; p = .034). These findings suggest that employees’ innovative behavior is driven primarily by direct leadership influences rather than by work-family processes. This study highlights the strategic importance of transformational leadership in fostering employee innovation in the FMCG industry.